Comprehensive profiling of metaplastic breast carcinomas reveals frequent overexpression of programmed death-ligand 1. Issue 3 (16th August 2016) - Joneja, Upasana; Vranic, Semir; Swensen, Jeffrey; Feldman, Rebecca; Chen, Wangjuh; Kimbrough, Jeffrey; Xiao, Nianqing; Reddy, Sandeep; Palazzo, Juan; Gatalica, Zoran
Abstract : Aims: Metaplastic breast carcinoma (MBC) is a rare subtype of breast carcinoma less responsive to conventional chemotherapy than ductal carcinoma. In molecular terms, MBCs usually cluster with triple-negative breast cancers (TNBCs), but have a worse prognosis than TNBCs. Studies investigating MBCs for specific biomarkers of therapy response are rare and limited by the methodological approaches. The aim of the present study was to characterise MBCs on a molecular level and test programmed death-ligand 1 (PD-L1) biomarker expression in MBCs for future therapeutic interventions. Methods: We profiled 297 samples (MBC (n=75), TNBC (n=106), human epidermal growth factor receptor 2 (HER2)-positive breast cancers (n=32) and hormone-positive breast cancers (n=84)) by next-generation sequencing. Immunohistochemistry for PD-L1 and programmed cell death 1 (PD-1) expression was performed using automated procedures. Results: The most commonly mutated genes in MBCs included TP53 (56%) and PIK3CA (23%). Pathogenic mutations in other genes, including HRAS, FBXW7, PTEN, AKT1 and SMAD4, were rare. PD-L1 expression was detected in a significantly higher proportion of MBCs (46%) than in other subtypes (6% each in hormone-positive and HER2-positive breast cancers, and 9% in TNBC, not otherwise specified, p<0.001). PD-1-positive tumour infiltrating lymphocytes (TILs) varied greatly in MBCs. Conclusions: Comprehensive profiling of a large cohort of this rare subtype of breast carcinoma highlighted the predominance of TP53 mutation and increased PD-L1 expression in carcinoma cells. These results can be exploited in clinical trials using immune checkpoint inhibitors.